An incidental discovery of a silent tracheal bronchus during flexible bronchoscopy: a case report and anesthetic perspective - Zou, Chaohui; Lv, Pinyi; Li, Xu; Yang, Qianwen; Liu, Lili (Frontiers in Pediatrics, 2026)
BackgroundA tracheal bronchus is a rare congenital anomaly of the tracheobronchial tree. Although often asymptomatic, its presence carries profound implications for airway management, particularly in anesthesiology. Unrecognized cases can lead to life-threatening complications such as ventilation failure and lobar collapse.Case reportWe report the case of a 5-year-old boy presenting with clinical and radiological features of left lower lobe bronchopneumonia. During a diagnostic flexible bronchoscopy performed under intravenous sedation-analgesia with preserved spontaneous ventilation, an anomalous right tracheal bronchus was discovered incidentally. This variant was entirely asymptomatic and contralateral to the infectious focus. The procedure was completed uneventfully, and the patient was discharged following successful medical management of Mycoplasma pneumoniae infection.ConclusionThis case highlights two critical aspects from an anesthetic perspective. First, it underscores the pivotal role of the anesthesiologist as a vigilant diagnostician in identifying clinically silent but high-stakes airway anomalies. Second, it demonstrates the utility of non-intubated sedation techniques in facilitating an unobstructed anatomical examination of the native airway. Proactive identification and documentation of such variants are essential for safeguarding future patient care.